Transient epidermal barrier deficiency and lowered allergic threshold in filaggrin‐hornerin (FlgHrnr−/−) double‐deficient mice. Issue 7 (15th April 2019) - Rahrig, Sebastian; Dettmann, Judith M.; Brauns, Birka; Lorenz, Verena N.; Buhl, Timo; Kezic, Sanja; Elias, Peter M.; Weidinger, Stephan; Mempel, Martin; Schön, Michael P.; Braun, Andrea
Abstract: Background: Filaggrin (Flg) and hornerin (Hrnr) share similar structural and functional features. Both proteins have been implicated as essential proteins for skin barrier maintenance. Loss‐of‐function mutations of these genes constitute a risk factor for atopic dermatitis and eczema‐related asthma. Furthermore, both FLG and HRNR protein levels are downregulated in patients with atopic dermatitis. Thus, mice deficient for Flg and Hrnr provide a novel model to study skin barrier impairment and the susceptibility for cutaneous inflammation. Methods: By using appropriate targeting vectors and breeding strategies, we established a homozygous FlgHrnr double‐deficient ( FlgHrnr −/− ) mouse model lacking both genes including the intergenomic sequence. Results: Neonates appeared normal, but developed a transient scaly phenotype with overall flaky appearance, but no overt skin phenotype in adulthood, thereby reflecting a subclinical barrier defect seen in humans. Structurally, FlgHrnr −/− mice displayed a markedly reduced granular layer and a condensed cornified layer. Functionally, FlgHrnr −/− mice showed permeability abnormalities and metabolic aberrations regarding the production of natural moisturizing factors (NMFs) in the stratum corneum . Surprisingly, although the immune system revealed no aberrations under steady‐state conditions, FlgHrnr −/− mice are predisposed to mount an allergic contact dermatitis, especially at hapten threshold levels eliciting allergic reactions. Conclusions: Together, our FlgHrnr −/− mouse model nicely reflects the epicutaneous sensitization susceptibilities and inflammatory reactions to environmental insults in humans with impaired skin barrier functions. Abstract : FlgHrnr −/− mice develop a transient flaky phenotype at young ages, but no overt skin phenotype in adulthood. The epidermis of FlgHrnr −/− mice exhibit structural (loss of keratohyalin granula), metabolic (loss of natural moisturizing factor), and functional (increased inside‐out penetration) abnormalities resulting in skin barrier deficiency. FlgHrnr −/− mice show increased susceptibility to allergic contact dermatitis (increased effector cell infiltration/hampered regulatory mechanisms). FlgHrnr‐/‐, Filaggrin‐Hornerin double‐deficient mice; KHG, keratohyalin granula; NMF, natural moisturizing factor